2017
DOI: 10.3390/polym9100525
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Structure Formation of Block Copolymer Thin Films during Thermal Solvent Vapor Annealing: Solvent and Thickness Effects

Abstract: Solvent vapor annealing of block copolymer (BCP) thin films can produce a range of interesting morphologies, especially when the perpendicular orientation of micro-domains with respect to the substrate plays a role. This, for instance, allows BCP thin films to serve as useful templates for nanolithography and hybrid materials preparation. However, precise control of the arising morphologies is essential, but in most cases difficult to achieve. In this work, we investigated the solvent and thickness effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…The fact that the 75/25 PS/PS‐ b ‐PNIPAM film requires more annealing time to become completely smooth is explained by the increased ratio of PS, which has a higher T g , close to the annealing temperature. As expected, in all cases, thermal annealing offers the required energy for chain rearrangement and leads to more ordered structures in the block copolymer films …”
Section: Resultssupporting
confidence: 75%
“…The fact that the 75/25 PS/PS‐ b ‐PNIPAM film requires more annealing time to become completely smooth is explained by the increased ratio of PS, which has a higher T g , close to the annealing temperature. As expected, in all cases, thermal annealing offers the required energy for chain rearrangement and leads to more ordered structures in the block copolymer films …”
Section: Resultssupporting
confidence: 75%
“…[31] Copyright 2014, American Chemical Society; V) Reproduced with permission. [35] Copyright 2017, MDPI; IX) Reproduced with permission. [33] Copyright 2006, Elsevier; VII) Reproduced with permission.…”
Section: The-state-of-the-art Phase-field Model To Simulate Phase Sepmentioning
confidence: 99%
“…Figure 1a lists a number of phase separation microstructures [28][29][30][31][32][33][34][35][36][37][38][39] in different polymer solutions. Figure 1a lists a number of phase separation microstructures [28][29][30][31][32][33][34][35][36][37][38][39] in different polymer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al employed a selective solvent during the SVA treatment of poly(methyl methacrylateblock-styrene) (PMMA-b-PS) and found that the resulting morphology depended on the swelling ratio of the segments [8]. According to Yang & Loose, for the poly(styrene-b-2vinylpyridine) (PS-b-P2VP) system, the obtained morphologies resulted in a perpendicular orientation with respect to the substrate surface only to film thickness of 0.4-0.8L o [9]. Nehache et al studied the triblock copolymer system poly(styrene-b-styrenesulfonic acid sodium salt-b-styrene) (PS-b-PSSNa-b-PS) dissolved at different compositions of tetrahydrofuran (THF)-water, finding the formation of a porous morphology at low and medium concentrations [10].…”
Section: Introductionmentioning
confidence: 99%